Verdensklasse eller blålys - Auken, Sune (Academic Quarter | Akademisk kvarter, 2011)
Sune Auken’s contribution to this volume, World Class or Will-o’-the-Wisp, discusses a new global narrative about the universities. A narrative that has become more and more worldwide and makes itself prevalent, and whose purpose is to apply the logics of business institutions to the universities in order to measure them better and to make them more useful. Auken questions the value of competition criteria derived from business organizations (competition between organizations) for the universities that have a different and complicated structure and other goals with their work. Moreover, he uncovers the incongruence and weaknesses behind the international university rankings. The article shows that despite the fact that universities today are permeated in management ideology they can still articulate a critique of the problematic aspects behind the process.